English Learning Material Based on Task-Based Instruction: A Study of Material Construction for Nursing Students - Risman Wanci (AL-ISHLAH: Jurnal Pendidikan, 2023)
Using the appropriate teaching approach in the teaching and learning process is an essential thing that a lecturer must consider. This research aimed to develop a syllabus, lesson plans, and English teaching materials for nursing students. This research applied research and development (R D). The writers used it to construct English instructional material for nursing students based on Task-Based Instruction. The steps in doing this research were; 1) perception, 2) needs analysis, 3) learning materials design, 4) product development, 5) expert validation, 6) implementation, 7) evaluation, 8) perception, 9) writing the final draft of the products. This research produced a syllabus, lesson plans, and coursebook materials. There are 14 units of material in the developed book, namely: 1) hospital, 2) admission to a hospital, 3) self-introduction, 4) health problems, 5) parts of the body, 6) asking and giving directions at a hospital, 7) checking vital signs, 8) individual patient assessment, 9) telling time and making a doctor’s appointment, 10) nursing instructions, 11) nursing tools, 12) discussion, 13) nursing seminar, and 14) job interview. The writers hoped the results could positively contribute to teaching and learning English for nursing in Indonesia, particularly at the Famika Nursing College of Makassar, Indonesia.